Early Implant Placement with Delayed Loading in Anterior Aesthetic Zone - A Case Report - Humagain, Manoj; Lamichhane, Simant; Subba, Mahima; Neupane, Manisha; Dawadi, Asmita (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
To prevent the sequelae of hard and soft tissue loss after tooth extraction, future need of bone augmentation procedures and utilisation of benefits during early stages of tissue healing, early implant promises to be an armoury for dental implantologists to perfectly simulate the natural dentition in anterior aesthetic areas. Here, a case of 30 years old male with a missing #11 (according to two-digit numbering system) planned for early implant placement and immediate temporisation with delayed loading is presented.